2019
DOI: 10.3390/ijerph16214162
|View full text |Cite
|
Sign up to set email alerts
|

Association of Internet Use with Attitudes Toward Food Safety in China: A Cross-Sectional Study

Abstract: A growing body of research has shown that people’s attitudes toward food safety is affected by their availability and accessibility to food risk information. In the digital era, the Internet has become the most important channel for information acquisition. However, empirical evidence related to the impact of Internet use on people’s attitudes towards food safety is inadequate. In this study, by employing the Chinese Social Survey for 2013 and 2015, we have investigated the current situation of food safety per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Changes in risk perception and CAE will evoke affection responses (usually fear), motivate information demand, and further induce actual information seeking behavior. Shan [36], Zhang [37]), and Terpstra [38] have confirmed that people in risky situations demonstrate more information seeking intentions and behavior. Hovick [11] and Wei [39] demonstrated the indirect and direct effect of risk perception on the information process.…”
Section: Risk Perception and Coping Appraisalmentioning
confidence: 85%
“…Changes in risk perception and CAE will evoke affection responses (usually fear), motivate information demand, and further induce actual information seeking behavior. Shan [36], Zhang [37]), and Terpstra [38] have confirmed that people in risky situations demonstrate more information seeking intentions and behavior. Hovick [11] and Wei [39] demonstrated the indirect and direct effect of risk perception on the information process.…”
Section: Risk Perception and Coping Appraisalmentioning
confidence: 85%
“…For example, Zhang et al [41] found that netizens have a lower evaluation of the government's environmental protection in China. Zhang et [52] suggested a negative correlation between Internet use and public food safety perception in China. Second, the results further support several previous studies on the impact of media exposure, especially social media, on public risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the reliability of the estimation results, several robustness checks are also conducted in this study. Generally speaking, methods used in previous studies for robustness checks mainly include: Substitution variable method, subdividing the samples and adopting different estimation methods, e.g., Zhang et al [52], Zheng et al [55]. Therefore, this paper mainly uses the following methods to conduct the robustness checks:…”
Section: Methods For the Robustness Checkmentioning
confidence: 99%
See 2 more Smart Citations